2017
DOI: 10.1111/trf.14283
|View full text |Cite
|
Sign up to set email alerts
|

Expediting red blood cell transfusions by syringing causes significant hemolysis

Abstract: Forceful manual syringing caused significant hemolysis and high free Hb concentrations. Pressurizing RBC bags induced no more hemolysis than after gravity-facilitated transfusions. Syringing to expedite RBC transfusions should be avoided in favor of pneumatic RBC bag pressurization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Neither veterinary study reported any adverse effects in the transfused patients. The present study did not show significant damage to the RBCs even after forceful aspiration of blood through the microaggregate 18‐μ filter followed by rapid infusion at a rate over 8,000 mL/h, contradicting findings of a similar human study 10 . Without reported adverse effects in vivo or significant hemolysis in vitro, rapid administration of blood via syringe bolus may represent an acceptable method of rapid transfusion in dogs, but in vivo studies are needed.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Neither veterinary study reported any adverse effects in the transfused patients. The present study did not show significant damage to the RBCs even after forceful aspiration of blood through the microaggregate 18‐μ filter followed by rapid infusion at a rate over 8,000 mL/h, contradicting findings of a similar human study 10 . Without reported adverse effects in vivo or significant hemolysis in vitro, rapid administration of blood via syringe bolus may represent an acceptable method of rapid transfusion in dogs, but in vivo studies are needed.…”
Section: Discussioncontrasting
confidence: 99%
“…Overzealous crystalloid administration may also lead to dilutional coagulopathy and worsening acidosis 3 . Massive transfusion protocols that ensure use of sufficient blood products are part of a multimodal approach to damage control resuscitation, which decrease mortality in hemorrhaging human trauma patients 4 There are numerous studies assessing different methods of rapid transfusion 5–10 and associated RBC damage. However, rapid infusion techniques have not yet been compared in veterinary medicine, so the comparable risk factors for hemorrhaging veterinary patients are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports of ex vivo hemolysis have implicated irradiation, catheter gauge, RBC washing, Cell Saver device suction, and high rate of infusion. [3][4][5][6][7][8][9][10] In addition, the one-way valve recently introduced into the operating room was suspected as a potential contributing factor. A series of in vitro experiments were performed to test the potential contribution of these factors.…”
Section: Resultsmentioning
confidence: 99%